The Effects of Long-term Growth Hormone Treatment on Ocular Findings - Eski, Mehmet Tahir; Teberik, Kuddusi; Bolu, Semih; Ankarali, Handan; Kaya, Murat; Arslanoglu, Ilknur (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose This study aimed to examine the long-term changes in anterior chamber depth (ACD), central corneal thickness (CCT), axial length (AxL), peripapillary retinal nerve fibre layer thickness (RNFLT), peripapillary ganglion cell layer – inner plexiform layer (GCL-IPL) thickness, and peripapillary choroidal thickness (ChT) after rhGH replacement treatment in paediatric patients with IGHD, compared to healthy controls.Methods Twenty-two children with IGHD including 12 girls and 10 boys were enrolled in the study group, and 30 (16 girls, 14 boys) healthy children composed the control group. A detailed ophthalmological examination was performed for each participant. ACD, CCT, AxL, peripapillary RNFLT, GCL-IPL thickness and ChT measurements were performed before the rhGH replacement treatment and in the 12th month of the post-treatment period, as well as the corresponding visits in the control group. AxL ultrasound pachymetry (CCT), peripapillary RNFL thickness, peripapillary RNFLT, GCL-IPL thickness, and peripapillary ChT parameters were measured by spectral-domain optical coherence tomography.Results The mean age of the groups were similar (p = 0.143). 12-month CCT, ACD, and AxL measurements of the study group showed significantly higher results than the pre-treatment measurements (p = 0.005, p = 0.024, and p = 0.002, respectively). Similarly, the mean RNFLT and ChT measurements of the study group obtained from all sectors were significantly higher in the 12th-month visit (p < 0.001 for both) other than the RNFLT, and GCL-IPL thickness measurements (p > 0.05 for all). However, all these parameters were similar at pre- and post-treatment visits in the control group (p > 0.05 for all). The mean pre-treatment values of all these parameters were significantly lower in the study group compared to the control group (p < 0.05 for all), other than the RNFLT, GCL-IPL thickness measurements (p > 0.05 for all), while the mean post-treatment values of all these parameters in both groups were similar at month 12 (p > 0.05 for all).Conclusion GH replacement treatment in childhood may play an important role in the development of the neural retina and can be effective on the anterior segment, RNFLT and ChT measurements.
Keywords: congenital isolated growth hormone deficiency; recombinant growth hormone; retina nerve fiber layer thickness; spectral-domain optical coherence tomography